2002
DOI: 10.1007/s00464-002-4204-7
|View full text |Cite
|
Sign up to set email alerts
|

Congenital double pyloric ostium in the adult

Abstract: Duplication of the pylorus, an extremely rare congenital anomaly of the stomach, consists of two openings connecting the antrum of the stomach to the duodenal bulb. Approximately 70 cases of double pylorus have been described in the literature, most of which are associated with the presence of chronic peptic ulcers, thus indicating an acquired origin of the condition. We report a case of congenital double pylorus in a 64-year-old man who complained about mild postprandial epigastric discomfort and nausea of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
8
0
2
Order By: Relevance
“…A congenital origin may be assumed if the diagnosis is made in early childhood; the histologic examination shows the presence of mucosa, lamina propria, and muscularis mucosae; or if surgical intervention, chronic penetrating ulcer, or chronic gastritis history is absent [5]. When peptic ulcer disease or gastric inflammation is the cause of gastric outlet anomaly, it generally presents as pyloric stenosis or double pylorus.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A congenital origin may be assumed if the diagnosis is made in early childhood; the histologic examination shows the presence of mucosa, lamina propria, and muscularis mucosae; or if surgical intervention, chronic penetrating ulcer, or chronic gastritis history is absent [5]. When peptic ulcer disease or gastric inflammation is the cause of gastric outlet anomaly, it generally presents as pyloric stenosis or double pylorus.…”
Section: Discussionmentioning
confidence: 98%
“…In pediatric studies, reported incidence is estimated to be 1 in 20,000-40,000 births, but incomplete obstructive lesions such as duodenal webs are even rarer, accounting for only 2% of these defects [6,7]. Although various rare types of gastric outlet anomalies including pyloric agenesis, pyloric stenosis, pyloric webs, duodenal webs, and Springer annular pancreas have been reported [1][2][3][4][5], in the English literature, we could not find any gastric outlet anomaly such as our patient's. In this case it was also interesting to see that with such an anomaly major gastric complaints were not present until the sixth decade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Schleimhaut ist glatt und reizlos, und das separierende Gewebe hat eher den Charakter eines runden Stranges oder Bandes [10]. Komplikationen treten hierbei kaum auf und die Patienten sind mit wenigen Ausnahmen [5,10] beschwerdefrei. In einem Fall war der Doppelpylorus mit einer Achalasie assoziiert [4].…”
Section: Der Doppelpylorusein Seltener Endoskopischer Befundunclassified
“…Frequently, it is a complication of peptic ulcer disease, resulting from penetration of the peptic ulcer and the creation of a fistula between the duodenal bulb and the prepyloric antrum. Occasionally it may be congenital or secondary to gastric carcinoma [3,4]. The location of the second duct is commonly in the lesser curvature of the gastric antrum, near the anatomic pylorus.…”
Section: To the Editorsmentioning
confidence: 99%